2017
DOI: 10.1590/1983-1447.2017.01.65409
|View full text |Cite
|
Sign up to set email alerts
|

Cuidado paliativo em oncologia pediátrica na formação do enfermeiro

Abstract: Objective: To identify and understand the view of students regarding palliative care in paediatric oncology during a graduate programme. Methods: Exploratory research with a qualitative approach conducted in a school of nursing in Rio de Janeiro. Data were collected from September to November 2014, through semi-structured interviews with 20 students enrolled in the last period of a graduate programme. The data were subjected to thematic analysis. Results:The results produced two thematic units: the (un)prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
32

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 10 publications
0
17
0
32
Order By: Relevance
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical exploration in the literature resulted in 17 publications (2,7,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . The studies were published between the years 2003 and 2017, with the largest volume of publications found in 2017 (2,(11)(12) , 2016 (7,(13)(14) , and 2013 (18)(19)(20) , with three studies in each year, which denotes the contemporaneity of the theme. Regarding the place of origin of the studies, it was observed that they were from several countries, with predominance of six articles from the United States of America (USA) (13,(15)(16)(17)20,25) , three from Brazil (2,7,12) , two from the United Kingdom (14,19) , two from India (11,22) , two from Canada (23)(24) , one from Argentina (21) and one from the Republic of Cyprus (18) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In nursing especially, the approach to the issue of death and palliative care during graduation is superficial, pointing to a vocational training lacking strategies to develop skills in this area, which are possible according to findings from other studies. 10 In this context, the challenge of the undergraduate nursing professor is to develop a better approach to education in respect to death that allows closer care of the patient and his/her relatives when faced with the end of life. In order to do this, professors should develop abilities to work with this theme, so courses should provide strategies that promote awareness and improve skills to deal with this theme.…”
Section: Introductionmentioning
confidence: 99%